Body mass index is associated with hypoglycaemia in children with acute vomiting and dehydration - Simona Tarnokova; Lenka Langerova; Sabina Szoradova; Barbora Pitekova; Tomas Dallos; Juraj Stanik (PLoS ONE, 2026)
Background Healthy children from 7 months to 7 years are known to be at risk for developing hypoglycaemia during prolonged fasting, particularly during acute illness with decreased oral intake. Our study aimed to identify additional factors associated with hypoglycaemia in children with acute vomiting and dehydration. Methods Our retrospective single-centre study included 560 healthy children and adolescents (aged 29 days to 17.96 years) without known metabolic disorders admitted to hospital with dehydration due to acute illness with vomiting or poor oral intake. Historical and anthropometric parameters were evaluated as potential factors associated with hypoglycaemia. Results A total of 171 (30.5%) participants (aged 0.6–10.7, median 3.8 years) experienced hypoglycaemia (≤3.3 mmol/l). Besides known factors such as a higher degree of dehydration (OR 2.505, 95% CI 1.532–4.095) and complete absence of oral intake (OR 2.185, 95% CI 1.331–3.586), additional factors independently associated with hypoglycaemia included diarrhoea (OR 0.178, 95% CI 0.068–0.468) and lower body mass index (BMI) (OR 0.011, 95% CI 0.000–0.605). Children with hypoglycaemia had a significantly lower BMI (median 14.29 vs 15.46 kg/m 2 , p < 0.001) than children without hypoglycaemia. Only one child with hypoglycaemia was obese. The highest rate of hypoglycaemia (37.5–51.6%) was observed in the 2–7-year age groups, who also had the lowest median BMI values (13.9–14.8). Conclusions Low BMI and absence of diarrhoea were associated with increased odds of hypoglycaemia. The typical BMI curve for children with physiologically low values at 2–7 years of age may partially explain the high incidence of hypoglycaemia in otherwise healthy children with decreased oral intake at this age.